The Interrelationship between Thermodynamics and Energetics: The True Sense of Equilibrium Thermodynamics - Starikov, Evgeni B. (Journal of Applied Solution Chemistry and Modeling, 2015)
The interrelationship between the conventional thermodynamics and energetics has been discussed in detail. A number of flavors has been considered in the field of energetics, with the conclusion that the actual difference among all of them is rather superficial. A need to reconsider the foundations of thermodynamics and statistical physics has been pointed out. Such a re-consideration ought to facilitate formulating thermodynamics at any level of matter organization: from the microscopic through nano- and mesoscopic to the macroscopic one.